Planteamiento de estrategia de comunicación, implementación y ejecución de la agencia de marketing digital Pacto - Espinoza Badillo, Michelle Jeanella (2024)
This document outlines the creation of the digital marketing brand, Pacto, along with the communication strategy devised for its market entry and formal establishment as a company. The process commences with a comprehensive qualitative market research phase, encompassing the conduct of two virtual focus groups and three in-depth interviews. Concurrently, the brand identity was developed, a pivotal process to set Pacto apart from its competitors. Throughout the creation journey, the company's value proposition was formulated, evolving as the brand integrated into the market and adjusted to identified needs. The most significant phase of the process unfolds with the formal launch of Pacto as a company, acquiring initial clients and generating the first profits. This document encompasses an assessment of Pacto's first year of activity, detailing internal processes, future projections, and valuable lessons learned. This analysis provides a clear and detailed insight into the trajectory and achievements of the company, emphasizing its commitment to entrepreneurship and its strategic approach to continued growth in the digital marketing market.